Relationship between Brain Natriuretic Peptide and Thromboembolic Events in Elderly Patients with Nonvalvular Atrial Fibrillation - Hongxia Wang; Jiajun Huang; Wenxi Gu; Xiaojiao Hao; Guiru Li; Yumin Yuan; Yingmin Lu (Cardiology Research and Practice)
Objective. To investigate the relationship between brain natriuretic peptide (BNP) and thromboembolic events in elderly patients with nonvalvular atrial fibrillation (NVAF). Methods. This is a prospective cohort study, and based on the inclusion and exclusion criteria, 180 elderly patients with NVAF were included. The patients received follow-up appointments in the clinic or by telephone every 6 months after the beginning of the study. The primary follow-up endpoints were thromboembolic and atherosclerotic events, including ischaemic stroke, myocardial infarction, and systemic embolism. The secondary endpoints were adverse events, including cardiovascular death, all-cause death, and hospitalisation for heart failure. Patients were divided into three groups according to their BNP level at admission: group A (BNP ≤334.5 pg/mL), group B (BNP = 334.5–1,288 pg/mL), and group C (BNP ≥1,288 pg/mL). Results. A total of 180 patients were enrolled in this study, with 50 patients in group A, 68 in group B, and 62 in group C. Compared with groups A and B, group C had a higher CHA2DS2-VASc score (Z = 15.142; P=0.001) and a lower ejection fraction (EF) value (Z = 119.893; P=0.001). The left atrium (LA) and left ventricular end-diastolic diameter (LVEDD) were larger (Z = 105.031; P=0.001 and Z = 74.430; P=0.001), respectively, suggesting that patients with significantly increased BNP had a higher risk of thromboembolism and atherosclerosis, lower EF, larger LA and LVEDD, and worse cardiac function. After 1 year of follow-up, the incidence of primary endpoint events (χ2 = 9.556; P=0.008) and secondary endpoint events (χ2 = 59.485; P=0.001) in group C were higher than those in groups A and B. Conclusion. Higher BNP levels may be an independent risk factor for thromboembolic and atherosclerotic events in elderly patients with NVAF. The higher the BNP level, the greater the risk of thromboembolic and atherosclerotic events.